2016
DOI: 10.1007/s12035-016-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I Induces Mitochondrial Protection through an Nrf2-Dependent Mechanism in Paraquat-TreatedHuman Neuroblastoma SH-SY5Y Cells

Abstract: Tanshinone I (T-I; 1,6-Dimethylnaphtho[1,2-g][1]benzofuran-10,11-dione; CHO), which may be found in Salvia miltiorrhiza Bunge (Danshen), is a potent anti-inflammatory, antioxidant, and anti-cancer agent. At least in part, T-I exerts antioxidant activity by activating signaling pathways associated with the maintenance of the redox state in mammalian cells. In this context, the upregulation of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) has received attention regarding the role of this transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…Nrf2 expression plays an important role in modulating the expression of some GSH-related enzymes, especially GCL and GR. ( 50 , 51 ) Nrf2 down-expression blocked the GCL expression induced by isorhamnetin. ( 52 ) Down-expression of Nrf2 also decreased GR activity and mRNA expression, and reduced GSH content in fish gill with amino acid phenylalanine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 expression plays an important role in modulating the expression of some GSH-related enzymes, especially GCL and GR. ( 50 , 51 ) Nrf2 down-expression blocked the GCL expression induced by isorhamnetin. ( 52 ) Down-expression of Nrf2 also decreased GR activity and mRNA expression, and reduced GSH content in fish gill with amino acid phenylalanine deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2 results in the induction of many cytoprotective proteins including HO-1, SOD1, and SOD2, etc. ( Higdon et al, 2012 ; de Oliveira et al, 2017 ). This notion is supported by the present study, in which acacetin activates Nrf2, induces the expression of HO-1, SOD1, and SOD2 and exerts protection of cardiomyocytes against hypoxia/reoxygenation insult.…”
Section: Discussionmentioning
confidence: 99%
“…Although HIBD is a complex multifactorial disease, a growing body of evidence has shown that oxidative damage to vital cellular structures plays a critical role in the pathogenesis of brain damage in both the immature and mature nervous system [ 6 , 41 , 42 ]. Several studies have indicated that TsI is able to exert antioxidative and antiapoptotic effects in cellular and mouse model of Parkinson’s disease (PD) [ 18 , 19 , 43 ]. In full agreement with these findings, we here found that treatment with TsI markedly reversed the decrease of antioxidants and the increase of pro-oxidants induced by HIBD in neonatal rats (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…5 and 6 ). The exact underlying cellular and molecular mechanisms remain to be determined, but may be at least in part due to the up-regulating effects of TsI on nuclear factor erythroid-2-related factor 2 (Nrf2), since previous studies have supported that the antioxidation of TsI is involved in Nrf2 signaling pathway both in vitro and in mouse model of PD [ 43 , 44 ]. Thus, future experiments examining Nrf2 signaling pathway in neonatal HIBD animals with or without TsI treatment will help determine whether the therapeutic effects of TsI in neonatal HIBD rats can be attributed to its up-regulation of Nrf2.…”
Section: Discussionmentioning
confidence: 99%